Layered Double Hydroxides Containing an Ionic Liquid: Ionic Conductivity and Use in Composite Anion Exchange Membranes. Issue 19 (23rd July 2018) - Pizzoferrato, Roberto; Ciotta, Erica; Ferrari, Ivan V.; Narducci, Riccardo; Pasquini, Luca; Varone, Alessandra; Richetta, Maria; Antonaroli, Simonetta; Braglia, Michele; Knauth, Philippe; Di Vona, Maria Luisa
Abstract: Zinc‐aluminum layered double hydroxide (LDH) containing an ionic liquid, 1‐butyl‐3‐methylimidazolium hydrogen sulfate (BmimSO4 ), has been synthesized by a co‐precipitation method. This strategy enabled the intercalation of the ionic liquid (IL) into the interlamellar space of LDH with the aim of increasing the ionic conductivity and reducing its dependence on water content. Pure and IL‐intercalated LDHs have been characterized by Fourier‐Transform Infrared (FTIR) spectroscopy and X‐ray diffraction. Electrochemical Impedance Spectroscopy (EIS) measurements showed that the addition of IL enhanced the ionic conductivity of LDH by a factor of 15 at low humidity and by a factor of 9 at high humidity conditions. As a possible application, LDHs were dispersed as a guest filler in a composite anion exchange membrane (AEM) based on polysulfone‐DABCO. In this case, the addition of IL remarkably improved the ionic conductivity of the membrane from 1.0 ⋅ 10 −9 to 2.4 ⋅ 10 −7 S/cm at low humidity. At high humidity, the membranes reached a conductivity of 25 mS/cm at 25 °C in OH form. Stability tests of composite AEM confirmed the positive effect of LDH nanoparticles. Abstract : Zinc‐aluminum layered double hydroxide (LDH) containing an ionic liquid is synthesized by a co‐precipitation method, enabling the intercalation of the ionic liquid (IL). The addition of the ionic liquid enhances the ionic conductivity. LDHs were dispersed as a guest filler in a composite anion exchange membrane (AEM). The addition of IL remarkably improves the ionic conductivity of the membrane. Stability tests of composite AEM confirmed the positive effect of LDH nanoparticles.